Diseño de un modelo de gestión de mantenimiento basado en la gestión del conocimiento para la dirección de sistemas de bombeo GAM del Instituto Costarricense de Acueductos y Alcantarillados. - García-Rodríguez, Ariel (Instituto Tecnológico de Costa Rica, 2018)
Maintenance management is a very important issue, however, in many cases people think that the most important is the technical part, but this project explains how to perform a maintenance using one of the resources forgotten by the engineers or managers of the Maintenance department. The forgotten resource is knowledge, the use of data and tacit knowledge; When this resource is known to filter and analyze it provides us with knowledge to learn to predict failures, to better organize financially, to perform tasks with more impact on the useful life of the equipment, among others. This project tries to establish a management mechanism for industrial maintenance management using knowledge as the main resource.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Gestión; Mantenimiento; Conocimiento; Datos; Mantenimiento predictivo; Organización; Research Subject Categories::TECHNOLOGY::Engineering mechanics